86.1k views
1 vote
Make x the subject
thank you​

Make x the subject thank you​-example-1

1 Answer

3 votes

Answer:


x =\sqrt{(a^6m)/(b^2)+n}

General Formulas and Concepts:

  • Order of Operations: BPEMDAS
  • Equality Properties
  • Exponent Power Rule:
    (b^m)^n=b^(mn)

Explanation:

Step 1: Define equation


a\sqrt{(x^2-n)/(m) } =(a^2)/(b)

Step 2: Solve for x

  1. Multiply a on both sides:
    \sqrt{(x^2-n)/(m) } =(a^3)/(b)
  2. Square both sides:
    (x^2-n)/(m) =((a^3)/(b))^2
  3. Simplify:
    (x^2-n)/(m) =(a^6)/(b^2)
  4. Multiply m on both sides:
    x^2-n =(a^6)/(b^2)m
  5. Add n to both sides:
    x^2 =(a^6)/(b^2)m+n
  6. Simplify:
    x^2 =(a^6m)/(b^2)+n
  7. Square root both sides:
    x =\sqrt{(a^6m)/(b^2)+n}
User Kauedg
by
5.6k points